Some implications of micro pricesetting evidence for inflation dynamics and monetary transmission - Luca Dedola; Erwan Gautier; Anton Nakov; Sergio Santoro; Emmanuel de Veirman; Lukas Henkel; Bruno Fagandini (European Central Bank (ECB), 2023)
This paper analyses the implications of the evidence on micro price setting gathered by Price-setting Microdata Analysis Network (PRISMA) for inflation dynamics and monetary policy, relying on calibrated models and direct empirical evidence. According to models calibrated to the euro area micro evidence in Gautier et al. (2022, 2023), infrequent price changes and moderate state dependence in price setting should result in a meaningful Phillips curve in the euro area. Empirical estimates of the Phillips curve during the low-inflation period confirm previous findings of a relatively flat but stable slope. This estimated flat slope reflects both infrequent and subdued price adjustment in response to aggregate shocks, i.e. the presence of nominal and real rigidities. Model-based simulations show that, due to non-linearities in price setting, changes in trend inflation above 5-6% would have significant effects on the euro area Phillips curve. Similarly, shocks to nominal costs larger than 15% would result in non-linear effects on inflation dynamics in calibrated models. In line with these simulations, recent micro evidence suggests that the return of higher and more volatile inflation seems to be associated with higher frequencies of price changes, mainly because the frequency of price increases rises with the level and volatility of inflation.
Keywords: E3; E5; 330; state-dependent price setting and non-linearities; heterogeneity; real andnominal rigidities; price Phillips curve